2018
DOI: 10.3389/fnut.2018.00039
|View full text |Cite
|
Sign up to set email alerts
|

Three-Month Feeding Integration With Bifidobacterium Strains Prevents Gastrointestinal Symptoms in Healthy Newborns

Abstract: Infantile functional gastrointestinal disorders are common in the first months of life. Their pathogenesis remains unknown although evidences suggest multiple independent causes, including gut microbiota modifications. Feeding type, influencing the composition of intestinal microbiota, could play a significant role in the pathogenesis. Previous studies supported probiotic supplementation success against colics, however mainly Lactobacillus spp. were tested. The aim of this study was to evaluate the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 69 publications
1
33
0
Order By: Relevance
“…Accordingly, bifidobacteria strains are utilized as probiotics for infant health and well-being [39]. Among the different species of the Bifidobacterium genus, B. breve has been formulated for clinical trials in pediatrics [40][41][42] and used as a supplement in infant formulas [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, bifidobacteria strains are utilized as probiotics for infant health and well-being [39]. Among the different species of the Bifidobacterium genus, B. breve has been formulated for clinical trials in pediatrics [40][41][42] and used as a supplement in infant formulas [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately 16 studies were included [19,[33][34][35][45][46][47][48][49][50][51][52][53][54][55][56], the majority of which (n = 7) were conducted in Italy [19,33,45,46,49,50,54]. Intervention sponsorship was not specified for seven studies [19,45,47,48,50,51,53] and two trials [46,52] were financed by governmental institutions.…”
Section: Study Patient and Treatment Characteristicsmentioning
confidence: 99%
“…Ultimately 16 studies were included [19,[33][34][35][45][46][47][48][49][50][51][52][53][54][55][56], the majority of which (n = 7) were conducted in Italy [19,33,45,46,49,50,54]. Intervention sponsorship was not specified for seven studies [19,45,47,48,50,51,53] and two trials [46,52] were financed by governmental institutions. There were 14 double-blinded studies [19,34,35,[45][46][47][48][49][50][51][52][54][55][56], one single-blinded [53] and in one review, the blinding was not specified [33].…”
Section: Study Patient and Treatment Characteristicsmentioning
confidence: 99%
“…Preliminary results showed that administration was effective in reducing minutes of daily crying. The clinical trial was then completed (155 infants, 130 breast-and 25 bottle-fed) as described in Aloisio et al [129]; the B. breve mixture was able to prevent gastrointestinal disorders in healthy breast-fed infants, principally by reducing 56% of daily vomit frequency, decreasing 46.5% of daily evacuation over time and improving stool consistency. The strength of this study is the interrelation among a prolonged probiotic treatment, several clinical and anthropometric parameters (e.g.…”
Section: B Breve Application In Clinical Trials In Pediatricsmentioning
confidence: 99%
“…Epidemiological data have shown the predisposition of neonates born by caesarean section to develop obesity later in life [130,131]. However, the B. breve supplementation in infants born by caesarean section [129] resulted in a lower catch-up growth in weight, thus allowing the Authors to speculate a protective effect of the probiotic strains against the risk to develop metabolic disturbance later in life. The efficacy of the same B. breve association was also shown in children affected by celiac disease.…”
Section: B Breve Application In Clinical Trials In Pediatricsmentioning
confidence: 99%